Surgery for Chronic otitis media with cholesteatoma: 10-year review - Bessa, Simão; Nogueira, Noémi; Gonçalves, Débora; Costa, Liliana; Lousan, Nuno (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2025)
Introduction: Optimal surgical management for Chronic otitis media with cholesteatoma is controversial. Decisions regarding surgical approaches are still highly debated today. Analysing and comparing our experience may help us to expand our common knowledge and predict further outcomes facilitating the discussion and choice of treatment options. Objectives and methodology: The authors conducted a retrospective review of medical records regarding patients who underwent surgery for cholesteatoma from January 2012 to December 2022. Analysis was made regarding preoperative parameters, surgical approaches, hearing results, surgical findings and postoperative complications including relapses. Results: Ninety-four patients (97 surgical procedures) with chronic otitis media with cholesteatoma were included. Of these, 43 were submitted to a canal-wall-down mastoidectomy, 52 to a canal-wall-up and 2 were managed with an atticotomy. Regarding tympanoplasties, 21.6% underwent a Portmann type 1 procedure, 41.2% a type 2 and 37.1% a type 3. There was an average pure tone average loss of 0.2 dB for wall-up procedures and 1,1 dB for wall-down with an average improvement of 11.8 dB for atticotomies. The overall relapse rate was 21.6% with 9.3% in the wall-down group, 30.8% in the wall-up group and 50% in cases where an atticotomy was performed. Conclusion: Cholesteatoma surgery requires a highly individualized assessment that considers the extension of the disease, audiometric parameters, surgeon experience and patient receptivity. This study revealed no significant difference in hearing results for both wall-up and wall-down while it favors wall-down surgeries for a safer eradication of the disease.